1/cosecA+cotA=cosecA-cotA
Answers
Answered by
14
your answer is here ✌✌✌✌✌✌
Attachments:
![](https://hi-static.z-dn.net/files/ddb/1a9d1893c8a69b333b6b3e2da436445c.jpg)
Answered by
6
Hi ,there !!!
here is your answer !!
we know that ,
cot² A + 1 = cosec²A
cosec² A - Cot²A = 1
(cosec A + cotA ) ( cosec A - cotA ) = 1
so ,
1 / cosecA + cotA = cosecA - cotA
hope it helps !!
thanks !!
Ranjan Kumar
here is your answer !!
we know that ,
cot² A + 1 = cosec²A
cosec² A - Cot²A = 1
(cosec A + cotA ) ( cosec A - cotA ) = 1
so ,
1 / cosecA + cotA = cosecA - cotA
hope it helps !!
thanks !!
Ranjan Kumar
Similar questions